Images of the Future of Young Refugees - Seyedeh Akhgar Kaboli (Siirtolaisuusinstituutti, 2025)
Images of the future are products of fears, hopes and anticipations developed by human beings in order to confront the uncertainty of the future. They influence their holders' decisions and behaviors and become evident when the future arrives. Unfolding the images of the future of refugees as a vulnerable social group provides a beneficial source of information for effective decision-making toward their empowerment. This article describes several factors affecting the images of the future of refugees and argues why images of the future of refugees must be investigated and contemplated.